1995
DOI: 10.1164/ajrccm.152.1.7599811
|View full text |Cite
|
Sign up to set email alerts
|

Variability of patient-ventilator interaction with pressure support ventilation in patients with chronic obstructive pulmonary disease.

Abstract: In 12 patients with chronic obstructive pulmonary disease (COPD) receiving pressure support ventilation (PSV), we studied the variability of respiratory muscle unloading and defined its physiologic determinants using a modified pressure-time product (PTP). Inspiratory PTP/min decreased as PSV was increased (p < 0.001), but there was considerable interindividual variation: coefficients of variations of up to 96%. On multiple linear regression analysis, 73 to 83% of the variability in inspiratory PTP was explain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
113
0
7

Year Published

1996
1996
2013
2013

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 279 publications
(125 citation statements)
references
References 0 publications
5
113
0
7
Order By: Relevance
“…The purpose of this part of the study was to establish whether or not during prolonged PPV-assisted walking respiratory muscle recruitment would reach the levels observed during free walking; as shown in table 3, this did not occur. This observation argues against the concept that exercise limitation in this context occurs as a result of a failure of the patient/ventilator interaction [29] and instead points to a physiological process. This could either be failure of the inspiratory muscle pump; this seems implausible since no trend for PTPoes or PTPdi to fall during PPV exhaustive exercise was observed.…”
Section: Significance Of the Findingsmentioning
confidence: 79%
“…The purpose of this part of the study was to establish whether or not during prolonged PPV-assisted walking respiratory muscle recruitment would reach the levels observed during free walking; as shown in table 3, this did not occur. This observation argues against the concept that exercise limitation in this context occurs as a result of a failure of the patient/ventilator interaction [29] and instead points to a physiological process. This could either be failure of the inspiratory muscle pump; this seems implausible since no trend for PTPoes or PTPdi to fall during PPV exhaustive exercise was observed.…”
Section: Significance Of the Findingsmentioning
confidence: 79%
“…Pressure support levels were set between 5 and 10 cmH 2 O in studies of weaning with PSV; such levels were suggested to be effective in overcoming the resistance and workload of endotracheal tube and respiratory circuits [26,[34][35][36][37]. SULZER et al [9] decreased minute volume to 25% of the baseline value in cardiac surgery patients and achieved extubation with this level of support.…”
Section: Weaning Protocols and Settingsmentioning
confidence: 99%
“…It has also been shown that at high levels of PSV many COPD patients show expiratory muscle activation during the inflation phase [32], indicating that the patient may be fighting the ventilator. In the present study this recruitment was recorded by the so-called expiratory increase in Pga, which has been shown to correlate with transversus abdominis EMG activity [17].…”
Section: Diaphragm Function and Breathing Patternmentioning
confidence: 99%